Safety and Efficacy of Antithrombotic Strategies in Patients With Atrial Fibrillation Undergoing Percutaneous Coronary Intervention - Untung, Untung; Rosita, Rosita (International Medical Journal Corp. Ltd, 2024)
Background: The landscape of antithrombotic strategies in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) has evolved significantly over the past decade, driven by the need to balance the prevention of thromboembolic events with the risk of bleeding. Literature Review: The literature on antithrombotic strategies for patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) reveals a nuanced landscape characterized by evolving treatment regimens aimed at balancing thromboembolic prevention and bleeding risk. The initial exploration identified significant gaps in the understanding of optimal therapies for AF patients post-PCI, highlighting the need for evidence-based approaches. Subsequent systematic reviews and meta-analyses. Conclusion: In conclusion, the evolving body of literature reflects a significant shift towards optimizing antithrombotic strategies for AF patients undergoing PCI. The consensus points to the need for individualized approaches that consider both thromboembolic and bleeding risks, with a growing preference for dual therapy involving NOACs. As research continues to advance, it is imperative that clinical guidelines are updated to reflect these findings, ensuring that patient care is informed by the most current evidence.